Evaluasi Manajemen Jurusan dalam Meningkatkan Kemampuan Menulis Skripsi Berbahasa Arab Mahasiswa Jurusan PBA FTK UIN Mataram - Muhammad Nurman (El-Tsaqafah : Jurnal Jurusan PBA, 2019)
This article aims to explain: (1) the factors that caused students ofthe PBA FTK UIN Mataram departemen difficulties in writing Arabic theses,(2) management of majors in improving the ability to write Arabic-languagethesis students of PBA FTK UIN Mataram departemen. The approach usedin this study was a qualitative approach with a case study design. The datasources in this study were students majoring in PBA departemen, PBA alumni,and permanent lecturers majoring in PBA. Data collection techniques usedwere interviews, documentation studies and observations while data analysiswas carried out using descriptive-qualitative analysis techniques. The resultsof this study are: (1) The causes of students majoring in PBA FTK UINMataram departemen difficulties in writing Arabic theses are (a) input,many PBA students come from high school or public school with minimalbasic language. (b) the willingness to speak Arabic in students is still low. (c)department policies are still not firm, namely still giving students the freedomto write Indonesian theses. (d) department facilities and infrastructureare still minimal, namely Arabic books or references are still lacking. (2)Management of majors in improving the ability to write Arabic theses forstudents majoring in PBA FTK UIN mataram namely (a) Growing interestand providing awareness to students. (b) Making policies requires studentsto write Arabic language theses and strive for students to communicate inArabic, at least when in PBA. (c) Making teaching materials for all subjects inPBA majors. (d) Implementing the IQF curriculum. (e) Carry out produckbasedpracticum activities. (f ) Making guidelines for Arabic thesis writing